2016
DOI: 10.1177/0735633116641694
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers’ Intention to Adopt Technology in Their Future Classrooms

Abstract: This study examined four factors that influence preservice teachers' intentions to adopt technology in classrooms based on the Theory of Planned Behavior and Technology Acceptance Model. These four factors-technology self-efficacy, attitudes toward technology, perceived ease of use of technology, and perceived barriers of technology adoption-were explored through a multiple regression analysis. The results indicated that technology self-efficacy, attitudes toward technology, and perceived ease of use of techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 52 publications
3
23
0
1
Order By: Relevance
“…In addition, students with high self-perceived IT competency used more mobile access to Moodle for interaction and collaboration activities. These seem to comply with many studies where experience and IT competency are positively associated with technology usage [9,14,24,26].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, students with high self-perceived IT competency used more mobile access to Moodle for interaction and collaboration activities. These seem to comply with many studies where experience and IT competency are positively associated with technology usage [9,14,24,26].…”
Section: Discussionsupporting
confidence: 87%
“…Instead, there is a relationship between basic and advanced tablet skills and students' intention to adopt mobile learning in the teaching of the natural sciences. This indicates that pre-service teachers' intentions to adopt new technology are not always supported by a minimum skill level in another technology tool (Li et al, 2016;Sugar et al, 2004). This finding also underscores the importance of teachers continually developing their ICT skills so that they can adopt and integrate new technologies into teaching.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of IATV includes but not limited to the attitudes of users towards the use of technology in education, pedagogical values and self-efficacy (Celik & Yesilyurt, 2013). Li, Li, & Franklin (2016) analyzed four aspects of IATV including technology self-efficacy (TS), attitudes toward technology (ATT), perceived ease of use of technology (PEUT), and perceived barriers of technology adoption (PBTA). Their results indicated that TS, ATT, and PEUT were significant in predicting IATV, whereas PBTA was found insignificant to predict IATV.…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 99%